7‐4: Late-News Paper: Holographic head‐up display with adaptive brightness of ambient light. Issue 1 (29th May 2019) - Liu, Yueda; Li, Yan; Chen, Quanming; Li, Sida; Su, Yikai
Abstract : We propose a holographic head‐up AR display with adaptive brightness of ambient tight based on geometry phase (GP) holographic lens and a cholesteric liquid crystal (CLC) film. By tuning the diffraction efficiency of a geometry phase (GP) holographic lens, the ratio of ambient light to virtual light is controlled to adapt to different driving environments. This approach provides a solution for more efficient and safer display for automobiles.